2007 6th IEEE and ACM International Symposium on Mixed and Augmented Reality 2007
DOI: 10.1109/ismar.2007.4538839
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Object Tracking for Augmented Reality Combining Graph Cuts and Optical Flow

Abstract: Figure 1: Tracking and annotating an object using graph cut segmentation. A building sign on the USC campus is first detected using simple recognition, after which no additional information is needed. As the camera moves, we segment and track the sign through significant scale and orientation changes, rendering an annotation above it. This example illustrates a possible navigation tool for exploring buildings on campus. In this case, the annotation tells the user that the building is Powell Hall, and that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Planned directions for future work include: the use of nonfiducial based registration methods (e.g. [4]; the use of more sophisticated rendering techniques and possibly 3D viewing; making use of advanced features of the physics engine; and allowing virtual objects to physically impact real ones (similarly to [1]).…”
Section: Discussionmentioning
confidence: 99%
“…Planned directions for future work include: the use of nonfiducial based registration methods (e.g. [4]; the use of more sophisticated rendering techniques and possibly 3D viewing; making use of advanced features of the physics engine; and allowing virtual objects to physically impact real ones (similarly to [1]).…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing a dilation of the previous graph cut's resultant binary image, the operations of function graph cuts ca be masked, resulting in a smaller graph on which to operate. Similar methods which use banded graph cuts, cutting only around the boundary of the object, have been proposed Lambaert et al (2005); Mooser et al (2007), however these methods have been shown to lose information and misclassify pixels in certain topologies Garrett & Saito (2008); Sinop & Grady (2006). Initial timing analysis of graph cuts shown in Fig.…”
Section: Focused Graph Cutsmentioning
confidence: 99%
“…This method produces good results and does not require a pre-existing model, but it does not run in real-time. Mooser et al [11] have built upon Lepetit and Berger's approach but use optical flow to transfer an object boundary into a new image.…”
Section: Related Workmentioning
confidence: 99%